Rifabutin Suppresses Inducible Clarithromycin Resistance in Mycobacterium abscessus by Blocking Induction of whiB7 and erm41 - Dinah Binte Aziz; Mei Lin Go; Thomas Dick (MDPI AG, 2020)
Clarithromycin (CLR) is the corner stone in regimens for the treatment of lung disease caused by Mycobacterium abscessus (Mab). However, many strains harbor the CLR-inducible CLR resistance gene erm41, encoding a ribosome methylase. Induction of erm41 is mediated by the transcription factor whiB7. We hypothesized that an inhibitor of RNA synthesis should be able to block the whiB7−erm41 induction response to CLR exposure and thus suppress CLR resistance. Recently, we discovered that the rifampicin analog rifabutin (RFB) shows attractive potency against Mab. To determine whether RFB-CLR combinations are synergistic, a checkerboard analysis against a collection of erm41 positive and negative Mab strains was carried out. This revealed synergy of the two drugs for erm41 positive but not for erm41 negative strains. To determine whether RFB’s potentiation effect was due to inhibition of the transcriptional induction of the whiB7−erm41 resistance system, we measured the effect of CLR alone and in combination with RFB on whiB7 and erm41 mRNA levels. CLR alone strongly induced whiB7 and erm41 expression as expected. The synergistic, growth-inhibiting combination of RFB with CLR blocked induction of both genes. These results suggest that RFB suppresses inducible CLR resistance by preventing induction of whiB7 and erm41 expression.